Psychometric Analysis of Eating Behaviors and BMI through TFEQ (Three Factor Eating Questionnaire) on Medical Students - Arif, Junaid; Shahzad, Asima; Latif, Abdul Rafey; Moeez, Abdul; Saleem, Hamza; Rahman, Zainab; Junaid, Ayesha (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess effects of eating behaviors on BMI using the three-factor eating questionnaire on medical students. Study Design: It was a quantitative analytical cross-sectional study. Replace and Duration of Study: The study was carried out among medical students of Rawalpindi and Islamabad Pakistan,from Jan till Apr 22. Methodology: A validated questionnaire (TFEQ) consisting of 51 questions was used to collect data online on 357 participants’ cognitive restraint, disinhibition, and hunger. Sample size was calculated using WHO sample size calculator keeping 95% CI.The participants in the study were students from various medical universities of Rawalpindi and Islamabad Pakistan. We calculated BMI values from the demographics (age, sex, and weight), and divided participants into 4 groups. Results: Rigid control and disinhibition both were positively related to BMI for the entire sample. There was a positive relationship between BMI and rigid control in females, while in male BMI was more positively related to disinhibition.Students characterized by both high disinhibition and high rigid control had significantly higher BMI than those by both low disinhibition and low rigid control. Hunger was also positively associated with BMI and effected both control and disinhibition (p≤0.000). Conclusion: The results show that all three eating behaviors i.e., disinhibition, hunger, and cognitive restraint, affect the BMI scores of students. High levels of restraint lead to higher disinhibition, which leads to increased weight. Rigid control also results in increased hunger which causes bouts of relapse eating (increased disinhibition)–all leading to increased BMI.